2017
DOI: 10.5796/electrochemistry.85.236
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Application to Efficient Annealing Process of CH<sub>3</sub>NH<sub>3</sub>PbI<sub>3</sub> Perovskite Crystalline Films

Abstract: As next-generation printable solar cells, perovskite solar cell utilizing organometal halide perovskite crystalline semiconductor as the active layer has been considered as one of the most promising systems for its high efficiency (>~22%) and construction with low-cost materials. Annealing process of organometal halide perovskite crystalline films are, however, relatively time-consuming process for the perovskite solar cells. We propose the microwave heating applied to the annealing process of the CH 3 NH 3 Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Pt NPs were deposited by DC sputtering on single crystals (size 5 mm × 5 mm) of the substrates, Al 2 O 3 (ε r ′ = 10), MgAl 2 O 4 (ε r ′ = 20), TiO 2 (ε r ′ = 110), and SrTiO 3 (ε r ′ = 310). We used single-crystal substrates to prevent uneven temperature distributions, which are often observed in MO x powders. , Single-crystal substrates can be used to accurately estimate the heat generated by the metal NPs because they have very few defects and, hence, do not undergo heating under MW irradiation. ,, The smooth and thin geometry of single-crystal substrates is more effective for ensuring uniform MW heating than packed beds of MO x powders. Furthermore, their low specific surface area prevents water adsorption, which often occurs in porous catalyst supports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pt NPs were deposited by DC sputtering on single crystals (size 5 mm × 5 mm) of the substrates, Al 2 O 3 (ε r ′ = 10), MgAl 2 O 4 (ε r ′ = 20), TiO 2 (ε r ′ = 110), and SrTiO 3 (ε r ′ = 310). We used single-crystal substrates to prevent uneven temperature distributions, which are often observed in MO x powders. , Single-crystal substrates can be used to accurately estimate the heat generated by the metal NPs because they have very few defects and, hence, do not undergo heating under MW irradiation. ,, The smooth and thin geometry of single-crystal substrates is more effective for ensuring uniform MW heating than packed beds of MO x powders. Furthermore, their low specific surface area prevents water adsorption, which often occurs in porous catalyst supports.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Single-crystal substrates can be used to accurately estimate the heat generated by the metal NPs because they have very few defects and, hence, do not undergo heating under MW irradiation. 4,31,32 The smooth and thin geometry of single-crystal substrates is more effective for ensuring uniform MW heating than packed beds of MOx powders. Furthermore, their low specific surface area prevents water adsorption, which often occurs in porous catalyst supports.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Microwaves are part of the electromagnetic wave, with a wavelength ranging from 1 m to 1 mm, which commonly converts energy from electromagnetic energy to thermal energy rather than heat transfer [105][106][107]. Several studies have demonstrated that microwaves also convey excellent control of perovskite crystallization [108][109][110][111].…”
Section: Electromagnetic Wave Annealingmentioning
confidence: 99%
“…Here we Please do not adjust margins Please do not adjust margins proposed, a microwave post-annealing treatment (MPAT) that can generate more homogeneous thermal domain to evaporate the solvent and the co-associated high frequency vibration can improve the Oswald ripening process by fusing the smaller crystals into the large crystallites. 35,36 Microwave is form of electromagnetic radiation with wavelengths ranging from one-meter to one millimeter. [21][22][23] In last 30 years, microwave treatment technology have a breakthrough achievement in photoelectron manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we demonstrated the use of microwave post-annealing treatment (MPAT) to form good quality mixed halide CH3NH3PbI3-xClx perovskite films. Applied MPAT resulted in more homogeneous thermal domain to evaporate the solvent and at the same time the coassociated high frequency vibration can improve the Oswald ripening process by fusing the smaller crystals into the large crystallites 35,36 Unlike the conventional annealing process at 100°C for 90 minutes, MPAT involves microwave post-annealing treatment (MPAT) where a perovskite absorber radiated with microwave based on the thermal annealing at 100°C for 70 minute. In this hybrid processing treatment, microwave treatment allows the formation of the homogeneous perovskite catalytic grains at regular intervals and the annealing enhance the high quality crystal growth.…”
Section: Introductionmentioning
confidence: 99%